Antibody-labelled gold nanoparticles synthesized by laser ablation to detect SARS-CoV-2 antigen spike - Sulfianti, Asri; Sopandi, Vidhia Tiara; Isnaeni, Isnaeni; Suryanggono, Jodi; Pambudi, Sabar; El Muttaqien, Sjaikhurrizal; Ningsih, Febby Nurdiya; Widayanti, Tika; Mardliyati, Etik; Annisa, Annisa (ADMET & DMPK, 2024)
Rapid detection test via lateral flow immunoassay (LFIA) is employed as an alternate method to detect Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Gold nanoparticles (AuNPs), a vital component of LFIA, can be synthesized by laser ablation technique. This intense laser radiation may result in monodisperse gold nanoclusters, which are impurity-free and demonstrate innovative biocompatible surface chemistry. In this current research, laser-ablated AuNPs are produced and coupled with an anti-spike SARS-CoV-2 monoclonal antibody (mAb) generated in our prior study. The AuNPs from 30,000 shots of laser ablation exhibited a robust red color with a maximum absorbance peak at 520 nm. The performance of AuNPs-mAb conjugates as a signal reporter was then evaluated in half-stick LFIA. The size distribution of AuNPs shows a relatively monodisperse and unimodal distribution with average particle diameters of 44.77 nm and a surface potential of -38.5 mV. The purified anti-spike mAb SARS-CoV-2 yielded two protein bands, representing the mAb heavy chain at 55 kDa and its light chain at 25 kDa. The immobilization of anti-spike mAb onto the surface of AuNPs revealed that 25 g/ml of mAb at phosphate buffer pH 9 was required to stabilize the AuNPs. The functional test of this conjugate was performed using dipstick LFIA, and the result shows that the AuNPs-mAb conjugates could successfully detect commercial spike antigen of SARS-CoV-2 at 10 ng level. In this study, laser-ablated AuNPs were functionalized with anti-spike mAb SARS-CoV-2 and successfully used as a signal reporter in half-stick LFIA for detecting antigen spike SARS-CoV-2.